2013
DOI: 10.1590/0102-311x00169712
|View full text |Cite
|
Sign up to set email alerts
|

Saúde dos adolescentes: um estudo de base populacional em Campinas, São Paulo, Brasil

Abstract: We estimated the prevalence of chronic diseases and other health problems reported by adolescents in relation to social and demographic variables and nutritional status. This cross-sectional population-based survey analyzed data from the Health Survey in Campinas, São Paulo State, Brazil, 2008. We used descriptive statistics and associations between variables with the chisquare test. Prevalence of chronic diseases among adolescents was 19.17%, with asthma showing the highest prevalence (7.59%), followed by hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 28 publications
0
11
0
9
Order By: Relevance
“…Adolescentes e jovens, por serem considerados pessoas saudáveis, não são consideradas pessoas com necessária atenção à saúde, a não ser nas questões de saúde reprodutiva (Brasil, 2010). Infelizmente, há um entendimento que adolescentes raramente ficam doentes e o hábito de se justificar qualquer problema de saúde, seja físico ou mental, como comum ou característico dessa etapa da vida, limita a atenção à saúde dos adolescentes (Braz et al, 2013).…”
Section: Discussionunclassified
“…Adolescentes e jovens, por serem considerados pessoas saudáveis, não são consideradas pessoas com necessária atenção à saúde, a não ser nas questões de saúde reprodutiva (Brasil, 2010). Infelizmente, há um entendimento que adolescentes raramente ficam doentes e o hábito de se justificar qualquer problema de saúde, seja físico ou mental, como comum ou característico dessa etapa da vida, limita a atenção à saúde dos adolescentes (Braz et al, 2013).…”
Section: Discussionunclassified
“…Data produced by the National Household Sample Survey (PNAD), conducted in Brazil in 2017, found that about 93% of households had mobile devices 4 . In a survey conducted in Brazil, it was found that 86% of respondents search the internet for information about their health, a percentage this higher than to medical opinion or specialists that was 74% 5 .…”
Section: Introductionmentioning
confidence: 97%
“…There is a significant and progressive increase in the use of the internet by people with chronic health conditions, and these are the ones who most use the internet for health information when compared to other patients 6 . Chronic conditions begin gradually, have an indeterminate and long prognosis, and their duration and clinical conditions vary over time and require continuous care with frequent interventions that can be articulated through the use of technologies 5,7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerando que transtornos mentais relacionam-se a insatisfação corporal (Xie et al, 2010), as intervenções neste aspecto devem focar em indivíduos de risco, como os que expressam necessidade de dieta mesmo com peso adequado, além de aumentar o afeto positivo e apoio de pares e pais (Bearman et al, 2006 (Braz et al, 2013;Inchley, 2016;Sousa et al, 2010). Alguns sintomas -nervosismo, dificuldade para dormir e cansaço e exaustão -parecem variar entre as regiões da cidade.…”
Section: íNdice De Massa Corporal Imagem Corporal E Comportamentos Punclassified